2019
DOI: 10.1038/s41598-019-47246-w
|View full text |Cite
|
Sign up to set email alerts
|

GRP78 translocation to the cell surface and O-GlcNAcylation of VE-Cadherin contribute to ER stress-mediated endothelial permeability

Abstract: Increased O-GlcNAcylation, a well-known post-translational modification of proteins causally linked to various detrimental cellular functions in pathological conditions including diabetic retinopathy (DR). Previously we have shown that endothelial activation induced by inflammation and hyperglycemia results in the endoplasmic reticulum (ER) stress-mediated intercellular junction alterations accompanied by visual deficits in a tie2-TNF-α transgenic mouse model. In this study, we tested the hypothesis that incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 50 publications
(61 reference statements)
3
22
0
Order By: Relevance
“…O-GlcNAcylation is increased in various cellular stresses, including chemotherapy treatment and ER stress, directly influencing cell survival in cancer cells. It has been reported that DOX activates the HBP through the AKT/XBP axis, which can promote O-GlcNAcylation [42]. Moreover, a recent study has suggested that reducing O-GlcNAcylation in cancer cells leads to CHOP induction through the activation of the ER stress response, resulting in apoptosis [43].…”
Section: Discussionmentioning
confidence: 99%
“…O-GlcNAcylation is increased in various cellular stresses, including chemotherapy treatment and ER stress, directly influencing cell survival in cancer cells. It has been reported that DOX activates the HBP through the AKT/XBP axis, which can promote O-GlcNAcylation [42]. Moreover, a recent study has suggested that reducing O-GlcNAcylation in cancer cells leads to CHOP induction through the activation of the ER stress response, resulting in apoptosis [43].…”
Section: Discussionmentioning
confidence: 99%
“…GRP78 is predominantly located in the ER, and the induction of GRP78 is recognized as a marker of ERS (Lenin et al., 2019). Upregulated GRP78 protein was observed in rat testis after intraperitoneal injection of 10 mg/kg CIS for 5 days (Soni et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Pathway. Like PERK, ATF-6 is an ER transmembrane protein [89]. After dissociation of GRP78, ATF-6 translocates to the Golgi apparatus where it is cleaved and activated by the proteases Sit-1/2.…”
Section: Atf-6mentioning
confidence: 99%